Divided Government European Style? Electoral and Mechanical Causes of European Parliament and Council Divisions - Philip Manow; Holger Döring (Max Planck Institute for the Study of Societies, 2006)
Voters who participate in elections to the European Parliament tend to use these elections to punish their domestic governing parties. Many students of the EU therefore claim that the party-political composition of the Parliament should systematically differ from that of the Council. This study, which compares empirically the party-political centers of gravity of these two central political actors, shows that opposed majorities between Council and Parliament may have other than simply electoral causes. The logic of domestic government formation works against the representation of politically more extreme parties, and hence against more EU-skeptic parties in the Council. At the same time, voters in EP elections vote more often for these more extreme and more EU-skeptic parties. The different locations of Council and Parliament in the pro-/contra-EU dimension may thus be caused by two - possibly interrelated - effects: a mechanical effect, due to the translation of votes into seats and then into 'office', and thus also into Council representation, and an electoral effect in elections to the European Parliament. The paper discusses the implications of this finding for our understanding of the political system of the EU and of its democratic legitimacy. – – Regelmäßig scheinen Wähler Europawahlen dazu zu nutzen, ihre jeweilige nationale Regierung elektoral zu bestrafen. Viele Beobachter der Wahlen zum Europäischen Parlament gehen daher davon aus, dass die parteipolitische Ausrichtung des Parlaments systematisch von der des Ministerrats abweicht. Die vorliegende Analyse, die die parteipolitische Zusammensetzung dieser beiden zentralen europapolitischen Akteure empirisch vergleicht, zeigt, dass neben den elektoralen Ursachen auch andere Gründe für gegenläufige Mehrheiten zwischen Parlament und Rat verantwortlich sein können. Die Logik der Regierungsbildung auf nationalstaatlicher Ebene führt dazu, dass "zentristische" und damit eher europafreundliche Parteien überproportional stark im Rat vertreten sind. In Europawahlen hingegen geben Wähler häufig extremer positionierten, das heißt auch europaskeptischeren Parteien ihre Stimme. Die politische Distanz zwischen Rat und Parlament resultiert in der Pro/contra-EU-Dimension daher aus dem Zusammenwirken zweier, möglicherweise miteinander verbundener Effekte: elektoralen und "mechanischen" Gründen für divided government in Europa. Das Papier diskutiert die Implikationen dieses Befundes für unser Verständnis von der Funktionsweise der EU und ihrer demokratischen Legitimation.
Keywords: 300